Impact of plastic waste fiber and treated construction demolition waste on the durability and sustainability of concrete - Selvakumar Duraiswamy; Prakhash Neelamegam; M. VishnuPriyan; George Uwadiegwu Alaneme (Scientific Reports)
Abstract This study explores the mechanical and durability properties of Plastic-Fibre Reinforced Concrete, incorporating hand-shredded plastic fibers sourced from polyethylene bags and PET bottles. Evaluations, including compressive and split tensile strength tests, were conducted on M40 grade mixes containing plastic fibers and 100% treated Construction and Demolition Waste (CDW), comparing them with conventional concrete. The results demonstrate a significant enhancement in strength properties with the addition of 0.25%, 0.5%, 0.75%, and 1% plastic-fibres, alongside the complete replacement of coarse aggregate with CDW, particularly noticeable at both 7 and 28-day curing ages. Although higher fiber dosages led to a slight reduction in compressive by 7% at the optimum percentage of 0.25% of PE and 0.5% of PET, the flexural strengths and split tensile strength exhibited a proportional increase of 11.7% and 18%. Surface analysis via Scanning Electron Microscopy (SEM) and elemental composition determination using Energy Dispersive Spectroscopy (EDS) revealed minimal fiber damage post-exposure, confirming its efficiency and contribution to higher strength and reduced weight loss in optimum mix. This novel approach combines manually recycled plastic waste as fibers with treated CDW, enhancing concrete properties while promoting sustainability. Sustainability analysis indicates that utilizing 100% CDW and plastic fiber contributes to reduced energy consumption, lower carbon emissions, and economic benefits. These findings underscore the potential of integrating non-degradable plastics into concrete mixtures, combined with treated CDW, offering both environmental sustainability and enhanced performance advantages in construction materials.